2001
DOI: 10.1177/002199801772662208
|View full text |Cite
|
Sign up to set email alerts
|

Volatile-Induced Void Formation in Amorphous Thermoplastic Polymeric Materials: I. Modeling and Parametric Studies

Abstract: Void formation in polymeric materials is of critical importance in a wide range of process technologies such as composites manufacturing, polymer devolatilization and foam molding. A predictive model for volatile-induced void formation and growth during the processing of thermoplastic polymeric materials is presented. This model is comprehensive, incorporating the effect of material properties, such as surface tension and moisture solubility and diffusivity in these materials, and processing conditions and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Unfortunately, in the case of a process where high temperature regimes are present, such as hot-tool welding, resistance welding, induction welding and FricRiveting, volumetric defects will be inherently present [47], so one can only reduce their density but not fully eliminate them. It has been reported that PEI has a significant affinity for atmosphere moisture [48].…”
Section: Thermal Degradation Behaviour Of Friction Riveted Pei Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, in the case of a process where high temperature regimes are present, such as hot-tool welding, resistance welding, induction welding and FricRiveting, volumetric defects will be inherently present [47], so one can only reduce their density but not fully eliminate them. It has been reported that PEI has a significant affinity for atmosphere moisture [48].…”
Section: Thermal Degradation Behaviour Of Friction Riveted Pei Polymermentioning
confidence: 99%
“…While for the majority of the polymers it would negatively affect short-term mechanical properties, moisture does not considerably affect PEI strength [49]. Nevertheless, under high temperatures (T > T g ), high heating rates, and increasing heating time, desorption of moisture and other volatiles in the polymer structure can lead to nucleation and growth of voids [47], in addition to flaws associated with chain scissioning and entrapped air. The separation of these types of flaws is a very complex matter and is out of the scope of this work.…”
Section: Thermal Degradation Behaviour Of Friction Riveted Pei Polymermentioning
confidence: 99%
“…The effect is less pronounced for unidirectional pregreg, as this undulation is not present and hence less elastic energy is stored in the fiber bed [24]. Secondly, a well known source of deconsolidation is the thermal expansion of dissolved gas [25] and moisture [15,21,26,27] in the matrix, especially at high heating rates. Deconsolidation can easily be prevented by applying external pressure during heating [15,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…As void nucleation in the polymer can be assumed to occur instantaneously 43 and the rate of nucleation is proportional to the equilibrium number of critical size voids, 42 the probability of void nucleation can be calculated using the nucleation rate for any given spatial location and heating history.…”
Section: Void Formation Due To Residual Volatilesmentioning
confidence: 99%